Effects of Quadriceps Strengthening Exercise on Quadriceps Muscle Strength and Its Relation to Lower Extremity Lean Mass - Istingadah Desiana; Marina Annette Moeliono; Tertianto Prabowo (International Journal of Integrated Health Sciences, 2017)
Objective: To discover whether quadriceps resistance exercise could increase quadriceps strength as well as its relation to lower extremity lean mass. Methods: This study was a pre- and post- experimental study in which 36 participants with knee OA grade 2 and 3 were recruited. Assesment of leg lean mass and quadriceps strength was taken before and after intervention. Participants practiced quadriceps isotonic resistance exercise 3 times a week for 8 weeks. This study was conducted in Dr. Hasan Sadikin General Hospital, Bandung from September 2014 to February 2015.Results: After the intervention, an increase in quadriceps strength was seen but not in the lower extremity lean mass. Statistical analysis showed that there was no correlation between lower extremity lean mass and quadriceps strength.Conclusions: Quadriceps strength is found to increase after intervention. No increase is found in the lower extremity lean mass.Keywords: Osteoarthritis, leg lean mass, quadriceps strength, quadriceps strengthening exercise DOI: 10.15850/ijihs.v5n2.1010